(untitled) (Romano-arabica, 2025)
The two volumes of Bridging Cultures, Building Legacies through Arabic stand as a rich and rigorous Festschrift honouring Professor George Grigore – an eminent linguist whose work has shaped Arabic dialectology and intercultural scholarship. The editors gather an impressive international cohort of scholars who, through 39 articles, celebrate the professor’s academic career and intellectual legacy. In the foreword, the editors highlight Grigore’s foundational role in Romanian Arabic studies and his pivotal role in institutionalizing Arabic dialectology at the University of Bucharest. They further note his particular distinction in the study of Mesopotamian Arabic varieties and emphasize his dedication to intercultural understanding and his impact as a translator of seminal Arabic texts into Romanian, including the Koran, and fundamental works of Islamic philosophy such as al-Kindi, Ibn Rushd, Ibn ‘Arabi, Ibn Ṭufayl, Ibn Sīnā among others. After years of study and published works, Professor George Grigore received well-deserved acknowledgment by being elected President of the prestigious International Association of Arabic Dialectology (AIDA – Association Internationale de Dialectologie Arabe) for two consecutive terms between 2015 and 2024.